2021
DOI: 10.1111/tbj.14190
|View full text |Cite
|
Sign up to set email alerts
|

Post‐mastectomy surveillance of BRCA1 / BRCA 2 mutation carriers: Outcomes from a specialized clinic for high‐risk breast cancer patients

Abstract: Female BRCA1/BRCA2 mutation carriers may elect bilateral risk-reducing mastectomy.There is a paucity of data on yield of imaging surveillance after risk-reducing mastectomy. This retrospective study focused on female BRCA1/BRCA2 mutation carriers who underwent bilateral mastectomy either as primary preventative, or as secondary preventative, after breast cancer diagnosis. All participants underwent breast imaging at 6-to 12-month intervals after mastectomy. Data on subsequent breast cancer diagnosis and timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The reported germline I482* variant in BRCA1 gene was associated with familial ovarian cancer predisposition in German and Japanese populations [ 20 , 21 ]. Q1756fs*74 in BRCA1 gene was also observed in Italian, Israel, USA, Brazilian, Ukrainian, Polish and Czech population with familial breast and ovarian cancer [ [22] , [23] , [24] , [25] , [26] , [27] ]. The 3rd most frequent was Q934* which had been associated with epithelial ovarian cancer in Turkish population and; familial and non-familial ovarian cancer in Japanese and Argentinian [ [28] , [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 92%
“…The reported germline I482* variant in BRCA1 gene was associated with familial ovarian cancer predisposition in German and Japanese populations [ 20 , 21 ]. Q1756fs*74 in BRCA1 gene was also observed in Italian, Israel, USA, Brazilian, Ukrainian, Polish and Czech population with familial breast and ovarian cancer [ [22] , [23] , [24] , [25] , [26] , [27] ]. The 3rd most frequent was Q934* which had been associated with epithelial ovarian cancer in Turkish population and; familial and non-familial ovarian cancer in Japanese and Argentinian [ [28] , [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 92%
“…The current guidelines recommend continued annual chest wall examination after RRM, as the low residual risk does not appear to justify routine postmastectomy imaging. In one Israeli cohort study of 237 BRCA1/2 carriers, Kanana et al reported a surveillance protocol of physical examination with alternating ultrasound or MRI imaging every 6 months following RRM [110]. After 10-year surveillance, no breast cancers were diagnosed in 53 unaffected carriers who underwent bilateral RRM; however, 7% of 184 affected carriers developed a local recurrence.…”
Section: Postmastectomy Surveillancementioning
confidence: 99%